Pertumbuhan dan Distribusi Potongan Komersial Karkas Sapi Australian Commercial Cross dan Brahman Cross Hasil Penggemukan - Harapin Hafid H; R Priyanto (Media Peternakan, 2006)
This research was conducted to study the growth and distribution of carcass components of beef carcas from Australian Commercial Cross and Brahman Cross cattle. The number of animals used was 165 heads with the body weight range of 350 - 400 kg taken from feedlot fattening. To study the growth and development of carcass component, the equation alometric Huxley was used. The result showed that breed had not significant effect on wholesale cuts. The geometry estimation on the specification of traditional markets and special market showed also the differences on topside (traditional market) and flank (special market). Key words : distribution, wholesale cuts, Australian Commercial cross, Brahman cross, fattening